Enhancing research publications using Rich Interactive Narratives - Takeda, Kenji; Earl, Graeme; Frey, Jeremy; Keay, Simon; Wade, Alex D. (Philosophical Transactions of the Royal Society A, 2012)
It is desirable in many disciplines to include supplementary information to add value to research publications, particularly in digital form. The concept of interactive publications, in which the reader can browse and navigate through in a nonlinear manner, is one such medium that is explored in this paper. We describe the application of the Rich Interactive Narrative framework to provide such a mechanism in the fields of archaeology and chemistry, to supplement academic journal papers. This system provides both passive (pre-recorded) and active (user-led) interaction modes to navigate through data, including experimental datasets, maps, photos, video and three-dimensional models, and supports event-based audio and text narration. It includes an extensive authoring tool for deployment to the Web. We conclude by discussing the future possibilities of such a platform for e-science and scholarly communication.